HUBUNGAN DURASI PENGGUNAAN SMARTPHONE DENGAN NYERI LEHER - Winarni, Sri; Setywati, Emiliana Indah Eko; Kristianingsih, Yustina; Pratama, I Dewa Dede Sultan (JPK : Jurnal Penelitian Kesehatan, 2025)
Currently, many students use smartphones to support their learning activities or for hobbies and lifestyles. However, students use their smartphones more for social media and playing games than for studying. The results of a preliminary survey on December 15, 2023 on students of the Catholic Health College of St. Vincentius A Paulo Surabaya obtained data that 80% used smartphones for more than 2 hours a day. The purpose of this study was to analyze the relationship between the duration of smartphone use and the intensity of neck pain in students. This study uses a correlation design with a cross-sectional approach with the independent variable being the duration of smartphone use and the dependent variable being the intensity of neck pain. The population used were students of the Catholic Health College of St. Vincentius A Paulo Surabaya who met the inclusion criteria with a total of 126 respondents taken by simple random sampling. The measuring instrument used was a questionnaire. The results of the study obtained 126 respondents, most (75%) used smartphones for more than 3 hours outside of lecture hours, 41% experienced mild pain and statistical tests with Spearman's rank obtained p = 0.049 with r = + 0.176 which means there is a positive relationship with very low strength between the duration of smartphone use and the intensity of neck pain. It is important to provide education by the student affairs department of STIKES Katolik St. Vincentius A Paulo Surabaya about tips for using smartphones wisely and also the need for a variety of joint sports activities to improve fitness.